Trypanosoma brucei rhodesience: Variation in human serum resistance after transmission between bushbuck and domestic ruminants by Glossina morsitans morsitans - Moloo, S.K.; Grootenhuis, J.G.; Jenni, L.; Brun, R.; Meirvenne, N. van; Murry, M. (Elsevier, 1995)
The aim of the present work was to study the cycle of transmission of T. b rhodesiense clone Etat 1/10 by G. morsitans from an infected bushbuck (Tragelaphus scriptus) to a Boran steer (Bos indicus), a goat (Capra hirci) and, by tsetse, from the infected domestic ruminants to bushbuck. The sensitivity of the bloodstream tryyomastigotes from the bushbuck, the Boran steer and the goat during the course of infection, to human serum was determined. The sensitivity of trypanosomes from the mice at peak of parasitaemia and of metacyclic T. b. rhodesiense from the infected tsetse to human serum, was also determined.